PENERAPAN SANKSI TERHADAP KASUS TINDAK PIDANA PENCURIAN DALAM KUHP DENGAN UNDANG-UNDANG PERKEBUNAN DALAM PUTUSAN PENGADILAN SIMALUNGUN NOMOR 590/ PID.B/2019/PN SIM - Abastian Martua; Dian Adriawan DG Tawang (Fakultas Hukum Universitas Tarumanagara, 2020)
The application of sanctions in criminal cases involves one of the offenses stipulated in the Criminal Code in which all losses and penalties for the offense are regulated, but in the case of safeguards related to the losses incurred for the offense and less than Rp. 2,500,000, it will be included in minor criminal offenses which regulate further in the Supreme Court Regulation No. 2 of 2012, but in practice many cases of theft of tipiring but other legal rules are sought in order to rule out tiping as in reported cases relating to minor acts but it requires a lex specialist Act Invite Plantation to exclude tipiring. How the Problems of Trial in Light Elections Arise in Kuhp with the Housing Law in the Decision of the District Court Simalungun Number 590 / Pid.b / 2019 / PN Sim. The author uses normative legal research methods. This research is descriptive analysis. Source of data used are primary data obtained from sources and secondary data from the results of library studies.. The author of the Supreme Court and the Panel of Judges further proves the existence of PERMA No. 2 of 2012 to support the enforcement of acts of violence in each case and also to support the application of minor criminal offenses and the application of lex specialists and legislators to more content in making each law making. only take from the rules that already apply in society.